The positioning and negotiation of ethnic identities for young Chinese immigrants in an Australian context - Li, Yanxi; Belford, Nish (Journal of International Students, 2026)
This exploratory pilot study examines how three young Chinese immigrants in Melbourne negotiate their ethnic identities. Using semistructured interviews and thematic analysis within a positioning theory framework, we examined participants’ dual cultural perspectives. Three interrelated themes emerged: linguistic positioning, peer/community belonging, and intergenerational expectations. Participants described hybrid, hyphenated identities and fluidly navigated between Chinese heritage and Australian culture. They balanced language skills and diaspora networks to affirm their heritage, while everyday social interactions sometimes signaled outsider status, highlighting tensions between family expectations and a sense of belonging. Our findings highlight the contextual, agentive nature of identity negotiation. This study contributes in-depth insight into the complex identity processes of young Chinese immigrants, with implications for multicultural understanding and immigrant integration.